FACTORS RELATING TO THE SUCCESS OF WORKING MOTHERS IN EXCLUSIVE BREASTFEEDING, NORTH ACEH, INDONESIA - Nelva Riza; Ristiani; Maysyura (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
Exclusive breastfeeding means babies are only given breast milk without any other additional food. It is recommended for up to 6 months and breastfed as early as possible. Exclusive breastfeeding until the baby is six months old can protect the baby from various diseases that cause infant death. Apart from benefiting the baby, exclusive breastfeeding also helps the mother, namely reducing postpartum bleeding, reducing blood loss during menstruation, accelerating weight gain before pregnancy, and reducing the risk of breast cancer and uterine cancer. The research aims to look at the factors that influence the success of working mothers in providing exclusive breastfeeding in the Sampoiniet community health center working area, Aceh district. The research method uses analytical observational research using a cross-sectional research design. The number of samples in this study was 39 working mothers with babies aged 7-12 months in the Sampoiniet Community Health Center Working Area, North Aceh Regency, using total sampling techniques. The results of the study showed that there was a relationship between knowledge (p=0.03), family support (p=0.03), and availability of facilities (p=0.00) with exclusive breastfeeding. Suggestions for health workers can improve the quality of services in promoting the exclusive breastfeeding program and cross-sector collaboration to support the exclusive breastfeeding program. To husbands, the success of exclusive breastfeeding is determined by the role of the family, especially the husband